2003
DOI: 10.1200/jco.2003.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Occult Metastasis in Clinical Stage I Nonseminoma: A Systematic Review

Abstract: Several strong predictors for occult metastasis were identified. A risk-adapted treatment policy should be developed that incorporates all relevant predictors so that adjuvant therapy is targeted better to those with occult metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(79 citation statements)
references
References 62 publications
(36 reference statements)
0
75
1
3
Order By: Relevance
“…Histopathologic predictors of occult metastatic disease in nonseminomatous germ cell tumors have been previously studied in clinical stage I patients. 20 The studies, however, differ according to the treatment approach used. Metastatic disease either was defined by relapse rates in patients managed initially by surveillance, 9,10,13,15,21 or was determined by the presence of metastatic disease found on retroperitoneal lymph node dissection in patients who underwent surgical staging.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic predictors of occult metastatic disease in nonseminomatous germ cell tumors have been previously studied in clinical stage I patients. 20 The studies, however, differ according to the treatment approach used. Metastatic disease either was defined by relapse rates in patients managed initially by surveillance, 9,10,13,15,21 or was determined by the presence of metastatic disease found on retroperitoneal lymph node dissection in patients who underwent surgical staging.…”
Section: Discussionmentioning
confidence: 99%
“…NS stage I surveillance Retrospective series identified the histological presence of vascular invasion as the strongest predictor of relapse in stage I NSGCTs (Freedman et al, 1987;Vergouwe et al, 2003). Surveillance as a strategy for the management of stage I tumours was prospectively studied by the Medical Research Council and their results were published in 1992 (Read et al, 1992).…”
Section: Nonseminoma Stage Imentioning
confidence: 99%
“…Such patients are typically offered 'adjuvant' chemotherapy in the form of two cycles of BEP with subsequent recurrences uncommon indeed (Donohue et al, 1993;Spermon et al, 2002;Albers et al, 2003). Patients without evidence of nodal metastases demonstrate relapse rates between 10 and 13%, the vast majority of which are pulmonary in nature and occur within the first year.…”
Section: Nonseminoma Stage Imentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have shown that vascular invasion (VI) is the single most important prognostic factor regarding risk of relapse [14][15][16][17]. Without adjuvant treatment, the high-risk group (VI positive) has a 3-year relapse rate of approximately 50%, while low-risk patients (VI negative) have a relapse risk of 10 to 20% [1,3,[16][17][18][19][20][21][22].…”
Section: Prognostic Risk Factorsmentioning
confidence: 99%